2009
DOI: 10.1016/j.pharmthera.2009.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Cellular models for the screening and development of anti-hepatitis C virus agents

Abstract: Investigations on the biology of hepatitis C virus (HCV) have been hampered by the lack of small animal models. Efforts have therefore been directed to designing practical and robust cellular models of human origin able to support HCV replication and production in a reproducible, reliable and consistent manner. Many different models based on different forms of virions and hepatoma or other cell types have been described including virus-like particles, pseudotyped particles, subgenomic and full length replicons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 337 publications
0
16
0
Order By: Relevance
“…In the past few years, robust cellular model systems that support HCV infection, replication, and viral particle secretion have been developed (27). Using these systems, studies have shown that HCV, like other positive-strand RNA viruses, hijacks intracellular membranes, probably of diverse origins, to generate unique membranous platforms where HCV genome replication and viral particle assembly occur (20).…”
mentioning
confidence: 99%
“…In the past few years, robust cellular model systems that support HCV infection, replication, and viral particle secretion have been developed (27). Using these systems, studies have shown that HCV, like other positive-strand RNA viruses, hijacks intracellular membranes, probably of diverse origins, to generate unique membranous platforms where HCV genome replication and viral particle assembly occur (20).…”
mentioning
confidence: 99%
“…Some candidate anti-viral molecules which first require metabolic activation (e.g., phosphorylation) to function properly in vivo may test negative in the cultured cell lines due to the lack of pre-activation in vitro. On the other hand, some candidate molecules that screen positive in cultured cell lines may not exert antiviral activities in vivo due to being metabolized before they are able to function in target tissues [20]. Because of the lack of a suitable small animal model, only two NS3/4A-specific inhibitors have advanced into clinical applications at present [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Post-binding steps are followed by a lateral migration, and the interaction of the virus with claudin-1 and occludin that leads to the tight junctions integrity disruption and culminate in clathrin-dependent endocytosis of virus particles, their endosome membrane fusion and viral genome release. facilitated the discovery and characterization of new receptors involved in virus-cell attachment and entry [39][40][41][42] other than the CD81 and LDL-receptor [43][44][45], enabling the development of new viral targets and therapies [46].…”
Section: Virus Attachment and Penetrationmentioning
confidence: 99%